Copper Catalyzed Regioselective N – Alkynylation of Pyrazoles and Evaluation of the Anticancer Activity of Ethynyl‐ Pyrazoles. Issue 12 (30th March 2018) - Sau, Mohan Chandra; Rajesh, Y.; Mandal, Mahitosh; Bhattacharjee, Manish
Abstract: A copper‐catalyzed regioselective N‐alkynylation of unsymmetrically substituted pyrazoles from the reactions of pyrazoles with aromatic and aliphatic terminal alkynes under aerobic condition is reported here. The single crystal XRD structures of the N‐substituted pyrazoles confirm the regioselectivity. The cytotoxicity towards MDA‐MB 231 breast cancer cells of three of the alkynyl pyrazoles has been investigated. Abstract : A Cu(OAc)2 catalyzed regioselective alkynylation of unsymmetrically substituted method has been developed and preliminary studies of the cytotoxicity of three of the N‐alkynyl‐pyrazoles show that, they are toxic towards cancer cells.